Hunting the European hare (Lepus europaeus Pallas, 1778) and fox (Vulpes vulpes Linnaeus, 1758) in the Western forest-steppe of Ukraine - Volokh, Anatolii; Волох, Анатолій Михайлович; Волох, Анатолий Михайлович; Trach, I. (My University, 2018)
For most Ukrainian hunters, the European hare and fox are currently the main species of game animals (Fig. 1). Since the process of their bagging is associated with a long and pleasant stay in the natural environment, the opening of the hunting season for these species is perceived as a long-awaited holiday. To this we should add that the hare meat is very tasty, has a high nutritional value and is impossible to purchase in our shops. Therefore, almost all members of different hunting societies take part in the opening of hunting.
Keywords: agrocoenoses; dynamics; European hare; Lepus europaeus; hunting; forest-steppe; fox; Vulpes vulpes; population; Ukraine